The Effect of Work Stress on Employee Performance at PT. ISM Division Bogasari Flour Mils Jakarta - Kusumawati, Syahriani; Fa’uzobihi, Fa’uzobihi; Taryanto, Taryanto; Irawan, Pristanto Ria (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
The purpose of this study was to determine work stress on the work of PT. ISM Bogasari Flour Mils Jakarta Division This study uses quantitative descriptive methods with data collection techniques through the distribution of questionnaires, and library data. In this study using a saturated sampling method used a total of 38 employees of PT. ISM Division Bogasari Flour Mils Jakarta, using simple linear regression data analysis techniques. The results of this study show that there is no effect of work stress on the performance of PT employees. ISM Bogasari Flour Mils Jakarta Division, work stress variable has a low effect and has an influence contribution of 2.4% on employee performance variables. The results of this study are expected to contribute to future research.